2022
DOI: 10.3390/ijms23158719
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Treatment Ameliorates Brain Development and Behavioral Performance in a Mouse Model of CDKL5 Deficiency Disorder

Abstract: CDKL5 deficiency disorder (CDD), a rare and severe neurodevelopmental disease caused by mutations in the X-linked CDKL5 gene, is characterized by early-onset epilepsy, intellectual disability, and autistic features. Although pharmacotherapy has shown promise in the CDD mouse model, safe and effective clinical treatments are still far off. Recently, we found increased microglial activation in the brain of a mouse model of CDD, the Cdkl5 KO mouse, suggesting that a neuroinflammatory state, known to be involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 110 publications
(185 reference statements)
0
17
0
Order By: Relevance
“…For instance, liposomal preparations using olive pomace oil [ 26 ], dietary formulations with LUT [ 27 ], and ultra-micronized preparations [ 28 ] can all enhance the oral absorption and safety of LUT. Previous studies have shown that LUT possesses biological activities such as neuroprotection, anti-neuroinflammation, and the prevention of neuronal death [ 16 , 29 ]. LUT holds great promise for the treatment of brain-related disorders such as cerebral ischemia, Alzheimer’s disease, depression, and autism spectrum disorders [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, liposomal preparations using olive pomace oil [ 26 ], dietary formulations with LUT [ 27 ], and ultra-micronized preparations [ 28 ] can all enhance the oral absorption and safety of LUT. Previous studies have shown that LUT possesses biological activities such as neuroprotection, anti-neuroinflammation, and the prevention of neuronal death [ 16 , 29 ]. LUT holds great promise for the treatment of brain-related disorders such as cerebral ischemia, Alzheimer’s disease, depression, and autism spectrum disorders [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that LUT possesses a variety of pharmacological activities, such as anti-inflammation, anti-oxidation, anti-aging, neuroprotective, neurotrophic, and neurogenic actions [ 14 , 15 ]. LUT can enhance or even rehabilitate hippocampal neurogenesis, as well as promote dendritic spine maturation and reduce hippocampal neuronal death, thus providing neuroprotective effects against brain injury [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal systemic inflammation and brain neuroinflammation have been described in Rett syndrome and CDD in all three disorders. [106][107][108][109][110][111][112][113] In fact, Rett syndrome has been suggested to be an autoimmune disease. 114 Reduced FOXG1 expression in experimental models increases sensitivity of neurons to inflammatory stimuli.…”
Section: The Close Relationship Between Cdkl5 Foxg1 and Mecp2 At The ...mentioning
confidence: 99%
“…The activation of quiescent aNSCs and the proper self-renewal and differentiation capacity of aNSCs are important for the functional adult brain [12] , [13] . Several diseases, such as Intellectual Disability (ID) and Autism Spectrum Disorders (ASD), show impaired adult hippocampal neurogenesis [14] , [15] , [16] . The cytoarchitecture of the septal and striatal SVZ, as a region of neonatal neurogenesis, is often altered in ASD patients [17] .…”
Section: Introductionmentioning
confidence: 99%